Global Financial Crisis and its Impact on German Automotive Industry A Comparative Study on Daimler AG, Volkswagen Group, BMW AG - Mecová, Markéta; Brůna, Karel, 1973-; Pour, Jiří; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
The content of this diploma thesis is the issue of the impact caused by the Global financial crisis on the German car manufacturers -- Daimler AG, Volkswagen Group, and BMW AG. The work is divided into three chapters. The goal of this thesis is to conduct a financial analysis for the period from 2003 till 2014 with the aim to focus on the financial stability. In the first theoretical chapter, I describe methods of financial analysis, bankruptcy and credit scoring models, and the economic value added measurement. The second chapter is devoted to the global financial crisis and the German automotive sector. The third chapter consequently analyzes the financial performance of conglomerates on the basis of techniques described in the first chapter.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses